KEBERHASILAN STEK Morus Alba L MENGGUNAKAN URINE SAPI SEBAGAI ZAT PENGATUR TUMBUH - F. Silvi Dwi Mentari (Politeknik Pertanian Negeri Samarinda, 2019)
This study aimed to calculate the speed of growth characterized by the emergence of shoots and percentage of successful growth of mulberry cuttings cuttings given plant growth regulator cow urine. The study consisted of two treatments, namely: first treatment, mulberry cuttings soaked using cow urine by dissolving 50 ml of cow urine / 100 ml of water, and second treatment, mulberry cuttings soaked in pure cow urine without additional water. The results showed that immersion with cow urine in the first treatment (mulberry cuttings soaked using cow urine by dissolving 50 ml of cow urine / 100 ml of water) and second (soaking mulberry cuttings with pure cow urine) gave the same results in the speed of growth that showed speed buds appear on 6th day, while the best percentage growth of mulberry cuttings in the second treatment was 97% followed by the first treatment of 83%.